Developing an in vitro osteochondral micro-physiological system for modeling cartilage-bone crosstalk in arthritis - Smith, Kyra W. Y.; Fung, Stephanie L.; Wu, Hsin-Fang; Chiesa, Irene; Vozzi, Giovanni; De Maria, Carmelo; Gottardi, Riccardo (Frontiers in Immunology, 2025)
IntroductionArthritis, a disease affecting over 50 million adults in the United States, encompasses many different conditions involving joints and surrounding tissues. Disease development, progression, and subsequent treatment is dependent on many different factors, including the relationship between adjacent tissues and the immunological signals involved. A major contributor to disease regulation is the crosstalk between the cartilage and the bone in joints, as well as their reaction to immune factors such as cytokine signaling and macrophage mediation. Studying cartilage-bone crosstalk in arthritis development can be difficult, as controlling immunological factors in vivo is challenging, but in vitro models often lack multi-tissue relevancy.MethodsTo fix this, we developed an in vitro micro-physiological system using a biphasic bioreactor that supports modeling of multiple tissues. We generated cartilage and vascularized-bone analogs and combined them in the bioreactor to allow diffusion and signaling between them. Using this system, we directly induced inflammation in the cartilage region and studied how crosstalk between the two adjacent tissues contributed to disease progression.ResultsWe showed that conditioned media from pro-inflammatory macrophages generated a different inflammatory profile than a simple inflammatory cytokine cocktail. We also showed that the vascularized-bone region became inflamed in response to the cartilage inflammation, verifying crosstalk in the system and successfully modeling the relationship between cartilage and bone in an arthritic environment. DiscussionThis model can be used to further probe the crosstalk between bone and cartilage in arthritis, allowing researchers to tease out the effect of specific inflammatory agents or therapeutics in vitro.